Analysis of Factors Influencing E-Book Acceptance Using Technology Acceptance Model (TAM) - Indy Millenio Diez Sutanto; Asif Faroqi; Siti Mukaromah (Komunitas Dosen Indonesia, 2025)
Reading remains a fundamental cognitive activity, even in the digital era. E-books offer an accessible and flexible alternative to printed materials, especially in academic settings. However, their acceptance among students varies significantly. This study aims to investigate the key factors influencing students’ acceptance of e-books using the Technology Acceptance Model (TAM). Specifically, it examines the effects of perceived usefulness, perceived ease of use, attitude toward e-books, innovativeness, and perceived risk on behavioral intention. A quantitative method was employed by distributing structured questionnaires to 400 students at UPN